2010
DOI: 10.1212/wnl.0b013e3181f11deb
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone modifies the effect of APOE genotype on hippocampal volume in middle-aged men

Abstract: Background:The APOE ⑀4 allele is an established risk factor for Alzheimer disease (AD), yet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
(35 reference statements)
2
31
0
Order By: Relevance
“…Protective effects of androgens against the deleterious effects of the APOE ε 4 allele have been documented in both male and female mice [Raber et al, 2002]. Paralleling the animal model findings, we found a significant interaction of APOE genotype and testosterone with respect to hippocampal volume [Panizzon et al, 2010]. Having at least one ε 4 allele was associated with smaller hippocampal volume, but only in the subgroup with low testosterone (defined as >1 SD below the mean).…”
Section: Apoesupporting
confidence: 80%
“…Protective effects of androgens against the deleterious effects of the APOE ε 4 allele have been documented in both male and female mice [Raber et al, 2002]. Paralleling the animal model findings, we found a significant interaction of APOE genotype and testosterone with respect to hippocampal volume [Panizzon et al, 2010]. Having at least one ε 4 allele was associated with smaller hippocampal volume, but only in the subgroup with low testosterone (defined as >1 SD below the mean).…”
Section: Apoesupporting
confidence: 80%
“…On the other hand, in middle-aged men being ε4 allele carriers, the free testosterone level was positively associated with verbal episodic memory performance (story recall), whereas no association was observed in ε4 allele noncarriers [43]. Also individuals with both low free testosterone levels and at least one copy of the ε4 allele had smaller hippocampal volumes than men who had none or only one of these risk factors [44]. Interestingly, in a group of 816 Caucasian women, Fernández-Martínez et al [45] demonstrated that estrogen receptor polymorphisms are associated with mild cognitive impairment and AD in APOE ε4 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of ApoE isoforms to promote Aβ clearance depends on the different lipidation status between them, as the higher lipidation promotes Aβ clearance [75], whereas ApoE-ε4 carriers have a lower level of lipidation and therefore a lower ability to clear Aβ deposition [76]. Testosterone levels influence the hippocampal volume in ApoE-ε4 allele carriers such that those with low testosterone and ApoE-ε4 carriers have the smallest hippocampal volumes [77]. Like females, males with AD also show higher levels of LH compared to the age-matched controls without AD [78]; however, males experience much more modest increases [79].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%